The Lexicon of Global Evangelicalism: A Discourse Analysis of Gather25 - Enns, David K. (Journal of media and religion, 2025)
Gather25 was a 25-hour, globally streamed broadcast designed to mobilize a transnational evangelical audience. This study argues that Gather25’s discourse, amplified by the unique affordances of the livestreaming medium, strategically employs a standardized lexicon to construct a particular vision of global evangelical identity. Using terministic screens and critical discourse analysis (CDA), this research analyzes the event’s 151,000-word transcript. The analysis reveals five dominant discourse clusters – Revival & Awakening, Mission & Evangelism, Globalization, Persecution & Suffering, and Spiritual Warfare – that function as terministic screens, selecting a reality of missional urgency and deflecting theological or political complexities. The findings demonstrate how the livestream format itself, with its emphasis on liveness, participation, and spectacle, reinforces these rhetorical frames. Rooted in the legacy of Billy Graham but adapted for a networked age, Gather25 offers a prototype for how evangelicalism uses the affordances of digital media to forge a unified, action-oriented identity.